PERBANDINGAN TAFSIR TULIS DAN LISAN M. QURAISH SHIHAB TENTANG QS. AL-QALAM DALAM TAFSIR AL-MISBAH (ANALISIS CIRI KELISANAN ADITIF ALIH-ALIH SUBORDINATIF) - Muhammad Alwi, HS (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
This paper would like to present in a comparative analysis the interpretation made by M. Quraish Shihab about QS. al-Qalam. Comparison of interpretations in this paper will elevate the written and oral interpretation of M. Quraish Shihab at once, in this case the interpretation of writing will refer to the Tafseer of Al-Misbah, and the interpretation of the Oral will refer to the "Kajian Tafseer of Al-Misbah". What is interesting in the interpretation of M. Quraish Shihab is that even though it is done by the same person, there is a difference between the interpretation of the text and the oral interpretation of M. Quraish Shihab. The process of comparison of interpretations will be analyzed using the theory of orality, especially additive traits instead of subordinates. The question to be answered in this paper is how are the differences and similarities between M. Quraish Shihab's written and oral interpretations of surah al-Qalam? What causes these differences and similarities